Green Gentrification and Health: A Scoping Review - Jelks, Na’Taki Osborne (Int J Environ Res Public Health, 2021)
Urban greening initiatives are often linked to enhanced human health and wellbeing, but they can also be a driver of gentrification. To date, few studies have focused on how green gentrification shapes health. In this scoping review, we analyzed existing peer-reviewed research on how greening initiatives in gentrifying neighborhoods impact health, well-being, and health pathways (e.g., physical activity, affordable housing). Using a multi-step approach to scoping the literature (including searches in PubMed, JSTOR, and Google Scholar), we identified 15 empirical studies that met our inclusion criteria. We found studies focusing on green space use, physical activity, sense of community, safety, and self-reported health. Overall, longtime, marginalized residents are negatively impacted by green gentrification as they experience a lower sense of community, feel that they do not belong in green space, and, in many studies, use green space less often than newcomers. Overall, the research in this area is limited, and more studies on mental health and cardiovascular health markers could advance this literature. Based on the limited available evidence, we suggest that public health, urban planning, and parks professionals could collaborate to enhance the use of green space for marginalized residents and their feelings of inclusion in gentrifying areas.